Ocular Application of Oleuropein in Dry Eye Treatment: Formulation Studies and Biological Evaluation - Susi Burgalassi; Erica Zucchetti; Elena Birindelli; Silvia Tampucci; Patrizia Chetoni; Daniela Monti (MDPI AG, 2021)
Background. Oleuropein is already known for its numerous pharmacological properties, but its activity in the ocular field has not yet been investigated. The study aims to verify a possible use of oleuropein (OLE)-based eye drops both in terms of efficacy in dry eye syndrome and stability in aqueous solution. Methods. OLE was co-precipitated with HP-β-cyclodextrin, and the obtained complex was encapsulated into liposomes prepared by hydration of a lipid film composed of Lipoid S100 and cholesterol with different pH buffer solutions. The hydrated vesicles were shrunk by ultrasonication or extrusion. The preparations were characterized from the physicochemical point of view by subjecting them to differential scanning calorimetry, ATR-FTIR, dynamic light scattering analysis, and microscopy. Subsequently, OLE protective activity against hyperosmotic and oxidative stress on rabbit corneal epithelial cells (RCE) was evaluated. Results. The liposomal vesicles obtained after extrusion showed a tendency towards greater encapsulation efficiency (up to 80.77%) compared to that obtained by sonication, and the liposomes hydrated in pH 5.5 solution tended to incapsulate more than the neutral ones. Ultrasonication produced two-dimensional populations of liposomes, the largest of which reached 2149 nm. On the contrary, the extruded liposomes showed homogeneous diameters of about 250 nm. Complexation with cyclodextrin and subsequent encapsulation in liposomes greatly increased the OLE stability in aqueous solution, especially at 4 °C and for the extruded formulations. OLE aqueous solution (OLE7.4-sol, reference) and neutral extruded liposomes (F7.4-e) were well tolerated on RCE cells. Moreover, OLE was able to control the effects of hyperosmolarity on ocular surface cells and to prevent oxidative stress-induced loss of cell viability.